IMPLEMENTASI KERJASAMA SISTER CITY KOTA DENPASAR DENGAN KOTA MOSSEL BAY - Dara Azzahra; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This study discusses the implementation of the Sister City collaboration between the City of Denpasar and the City of Mossel Bay. In 2019, Denpasar and Mossel Bay signed an MoU which aims to form a Sister City Cooperation between the parties in order to promote and develop friendly relations by generating a scope of cooperation in the fields of Culture and Tourism Promotion, Creative Economy Development and Human Resource Capacity Building. The purpose of this study was to determine the implementation of sister city collaboration between Denpasar City and Mossel Bay City. This study uses a pluralism perspective, with a group-individual analysis level. This study also uses the theory of paradiplomacy cooperation and the concept of Sister City. The method used in this study is a qualitative method with data collection techniques using literature and various literature that refers to books, journals and sites on the internet. This research shows the form and implementation of activities during the Sister City collaboration which were still carried out several times. This was based on the covid-19 pandemic which caused the two cities to carry out restrictions and were unable to carry out cooperative activities offline. So that the activities of implementing the Sister City cooperation between Denpasar City and the City of Mossel Bay Program that have been carried out are the "Denpasar Room" and "Mossel Bay Room" through virtual videos that focus on the creative economy, human resources, smart city, and tourism fields. Keywords: Implementation, paradiplomacy, Sister City Cooperation